2007
DOI: 10.2486/indhealth.45.653
|View full text |Cite
|
Sign up to set email alerts
|

Concerns and Preparedness for an Avian Influenza Pandemic: A Comparison between Community Hospital and Tertiary Hospital Healthcare Workers

Abstract: Little is known about differences in levels of concerns or preparedness for an avian influenza (AI) pandemic among healthcare workers (HCWs) in different types of hospitals. We compared these concerns and preparedness between 326 HCWs of two community hospitals (CHs) and 908 HCWs from a tertiary hospital (TH) using a self-administered questionnaire between March-June 2006. Response rates were 84.2% and 80.0% from the CHs and TH. Most HCWs (71.6%) felt prepared for an AI outbreak and had significant concerns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 11 publications
4
62
0
Order By: Relevance
“…Koh et al compared clinical and personal preparedness among healthcare workers in Singapore and south Jakarta, Indonesia (16). Cheong et al compared flu concerns and preparedness against the employees at a hospital in Singapore (17). The general knowledge among our groups comparing with the studies of Southeast Asia is lower especially regarding self-protection equipment which was much lower in comparison with those studies (16).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Koh et al compared clinical and personal preparedness among healthcare workers in Singapore and south Jakarta, Indonesia (16). Cheong et al compared flu concerns and preparedness against the employees at a hospital in Singapore (17). The general knowledge among our groups comparing with the studies of Southeast Asia is lower especially regarding self-protection equipment which was much lower in comparison with those studies (16).…”
Section: Discussionmentioning
confidence: 57%
“…These comments could be due to a previous SARS experience in the Southeast Asia that made them more experienced and more prepared for diseases such SARS or any type of influenza (18). Also the government was more concerned and made a control plan for all hospitals, especially the public ones (8,9,17,19). Our study had several limitations.…”
Section: Discussionmentioning
confidence: 90%
“…During the pandemic and epidemic events that had occurred, social ostracism experienced by HCWs and their family was a prominent finding in previous studies, including a study conducted in Singapore in 2006 (63.5% and 51.9%, respectively) (21) , another study in 2007 (57.1% and 46.4%) (24) , and a study in Egypt during the H1N1 pandemic in 2009 (52.8% and 30.6%) (23) . However, our study revealed little concern on social ostracism among HCWs and their family regarding epidemic and pandemic events (24.5% and 17.5%, respectively), which is identical to the results of a study on avian influenza in South Jakarta (26) .…”
Section: Preparedness For Epidemic and Pandemic Events:-mentioning
confidence: 91%
“…Sample size:-Sample size was calculated for an alpha of 0.05, based on a 71.6% overall prevalence of perceived preparedness among HCWs, taken from a study conducted in Singapore in 2006 about concerns and preparedness for an avian influenza pandemic among HCWs (21) . The total population of the MOH hospitals in Jeddah was 8126 HCWs (22) .The sample size was 305 HCWs, which was estimated using OpenEpi version 3.03a.…”
Section: Study Design and Population:-mentioning
confidence: 99%
See 1 more Smart Citation